1999
DOI: 10.1089/thy.1999.9.119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transforming Growth Factor β1, β2, and β3 in Multinodular Goiters and Differentiated Thyroid Carcinomas: A Comparative Study

Abstract: The various isoforms of transforming growth factor-beta (TGFbeta) are growth-inhibiting cytokines for cells of epithelial origin. In malignant thyroid tumors, several studies documented a high expression of TGFbeta in the majority of thyroid follicular cells suggesting a possible role as an inhibitor of cell proliferation. In contrast to this uniform pattern of TGFbeta expression in thyroid cancer, scarce and controversial data have been reported on the expression of TGFbeta in benign multinodular goiter. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
5
26
0
6
Order By: Relevance
“…However, TGF-β and activin are overexpressed in several carcinomas (17,19,25). Similarly, we have previously shown high TGF-β and activin protein expression in thyroid cancer, while the expression in normal tissue is predominantly negative (20,21). Despite the increased expression of these proteins in neoplastic cells, loss of TGF-β/activin responsiveness is frequently observed in cancer (2).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, TGF-β and activin are overexpressed in several carcinomas (17,19,25). Similarly, we have previously shown high TGF-β and activin protein expression in thyroid cancer, while the expression in normal tissue is predominantly negative (20,21). Despite the increased expression of these proteins in neoplastic cells, loss of TGF-β/activin responsiveness is frequently observed in cancer (2).…”
Section: Discussionmentioning
confidence: 55%
“…Although both TGF-β and activin exert inhibitory effects on the proliferation of normal thyroid follicular cells, we have previously reported that thyroid tumors express the TGF-β isoforms, TGFβ-1, TGFβ-2 and TGFβ-3 as well as activin isoforms, activin A and activin B (20,21). An impairment of signal transduction has been identified in the development and progression of several epithelial cancers (17,22).…”
mentioning
confidence: 99%
“…Thyroid cancer is the most prevalent endocrine malignancy, papillary carcinoma being the most common thyroid carcinoma (DeLellis & Williams 2004). In previous studies, we observed TGF-b1, ActA, and also SMADs expression in thyroid neoplasms (Kimura et al 1999, Cerutti et al 2003. The co-expression of TGF-b1 and ActA does not permit us to distinguish the individual role of each of these growth factors in the thyroid.…”
Section: Introductionmentioning
confidence: 78%
“…Despite its anti-proliferative activity, expression of TGF-b1 is elevated in thyroid carcinomas, suggesting that tumor cells become unresponsive to the TGF-b inhibitory signal (Kimura et al, 1999). Although chromosomal deletions involving the SMAD4 locus are frequently found in pancreatic adenocarcinomas, metastatic colorectal cancers, and small intestinal carcinomas , these deletions are rarely observed in thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%